2021
DOI: 10.1016/j.ophtha.2021.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Use Associated with Refractive Error in Teenagers

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 35 publications
2
27
1
2
Order By: Relevance
“…Em uma pesquisa transversal de base populacional, realizada através de questionários preenchidos por participantes de 12 a 35 anos, foi revelado que os respondentes usavam seus dispositivos eletrônicos por mais de 5horas/dia, e que possivelmente isso estaria relacionado a alta prevalência de miopia e astigmatismo entre eles (BARROS et al, 2021). Em uma pesquisa parecida, realizada entres adolescentes holandeses de 12 a 16 anos, verificou-se que eles passavam quase 4horas/dia em seus smartphones e que episódios de contínuo foram associados a mais erros refrativos míopes (ENTHOVEN et al, 2021). Além disso, um estudo prospectivo observacional, iniciado no ano de 2000 e realizado com participantes de 16 e 17 anos, associou a atividade física por mais de 3horas/semana a uma redução de 40% nas chances de miopia, e o uso de dispositivos de tela por mais de 6horas/dia ao dobro de chances de adquirir o erro refrativo em graus leves (HANSEN et al, 2020).…”
Section: Discussionunclassified
“…Em uma pesquisa transversal de base populacional, realizada através de questionários preenchidos por participantes de 12 a 35 anos, foi revelado que os respondentes usavam seus dispositivos eletrônicos por mais de 5horas/dia, e que possivelmente isso estaria relacionado a alta prevalência de miopia e astigmatismo entre eles (BARROS et al, 2021). Em uma pesquisa parecida, realizada entres adolescentes holandeses de 12 a 16 anos, verificou-se que eles passavam quase 4horas/dia em seus smartphones e que episódios de contínuo foram associados a mais erros refrativos míopes (ENTHOVEN et al, 2021). Além disso, um estudo prospectivo observacional, iniciado no ano de 2000 e realizado com participantes de 16 e 17 anos, associou a atividade física por mais de 3horas/semana a uma redução de 40% nas chances de miopia, e o uso de dispositivos de tela por mais de 6horas/dia ao dobro de chances de adquirir o erro refrativo em graus leves (HANSEN et al, 2020).…”
Section: Discussionunclassified
“…Moreover, compared with primary and middle school students, high school students had less exercise time, more sedentary time, and worse mental health as a result of the higher requirements for study ( 50 , 51 ), which could weaken the relationship between PSU and BP. So far, the majority of literature only use screen time to explore the association between the use of electronic devices and adolescents' health ( 32 , 52 ). However, increasing researchers argued that researchers should not only focus on screen time when exploring the health impact of the use of electronic devices for adolescents ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, the survey results showed that the ametropia of students in Beijing was significantly related to lower level activities ( 37 ). In 2021, Dutch researchers surveyed 525 teenagers' smartphone use, which also showed that refractive errors were significantly correlated with behaviors ( 38 ). Orlansky's findings suggest that poor vision affects a wide range of areas, such as reading, writing, posture, and movement, which may increase the likelihood of bad behavior in adolescents with poor vision ( 39 ).…”
Section: Discussionmentioning
confidence: 99%